Sistem Informasi Akuntansi Koperasi Berbasis Web Pada KPN “Sehati” RSUD Kota Sungai Penuh - Ridwan, Muhammad; Devitra , Joni (LPPM Universitas Dinamika Bangsa, 2023)
The role of information technology in the business world is very important. Especially helping business people in managing their business well. One aspect that really needs the role of information technology is the financial aspect. Because in this aspect errors often occur if business actors still manage finances manually. This is what is being experienced by KPN